Patients’ Perspectives on Tapering of Chronic Opioid Therapy: A Qualitative Study - Frank, Joseph W.; Levy, Cari; Matlock, Daniel D.; Calcaterra, Susan L.; Mueller, Shane R.; Koester, Stephen; Binswanger, Ingrid A. (Pain medicine (Malden, Mass.), 2016)
Objective. There is inadequate evidence of long-term benefit and growing evidence of the risks of chronic opioid therapy (COT). Opioid dose reduction, or opioid tapering, may reduce these risks but may also worsen pain and quality of life. Our objective was to explore patients’ perspectives on opioid tapering. Design. Qualitative study using in-person, semistructured interviews. Setting and Patients. English-speaking, adult primary care patients (N = 24) in three Colorado health care systems. Methods. Interviews were audio recorded, transcribed, and analyzed in ATLAS.ti. We used a team-based, mixed inductive and deductive approach guided by the Health Belief Model. We iteratively refined emergent themes with input from a multidisciplinary team. Results. Participants had a mean age of 52 years old, were 46% male and 79% white. Six participants (25%) were on COT and not tapering, 12 (50%) were currently tapering COT, and 6 (25%) had discontinued COT. Emergent themes were organized in four domains: risks, barriers, facilitators, and benefits. Patients perceived a low risk of overdose and prioritized the more immediate risk of increased pain with opioid tapering. Barriers included a perceived lack of effectiveness of nonopioid options and fear of opioid withdrawal. Among patients with opioid tapering experience, social support and a trusted health care provider facilitated opioid tapering. These patients endorsed improved quality of life following tapering. Conclusions. Efforts to support opioid tapering should elicit patients’ perceived barriers and seek to build on relationships with family, peers, and providers to facilitate tapering. Future work should identify patient-centered, feasible strategies to support tapering of COT.